제주 흑우 집단에서 Indel, Microsatellite 마커와 MC1R 유전자형을 이용한 친자 확인 - 한상현; 조상래(농촌진흥청 축산기술연구소; 조인철; 조원모; 김상금; 양성년; 강용준; 박용상; 박세필; 김은영; 이성수; 고문석; et al. (Journal of animal reproduction & biotechnology (Online), 2013)
This study was carried out to examine a molecular marker system for parentage test in Jeju Black cattle (JBC). Based on the preliminarily studies, we finally selected for construction of a novel genetic marker system for molecular traceability, identity test, breed certification, and parentage test in JBC and its related industrial populations. The genetic marker system had eight MS markers, five indel markers, and two single nucleotide polymorphisms (SNPs;g.G299T and g.del310G) within MC1R gene which is critical to verify the breed specific genotypes for coat color of JBC differing from those of exotic black cattle breeds such as Holstein and Angus. The results showed lower level of a combined non-exclusion probability for second parent (NE-P2) of 4.1202×10-4 than those previously recommended by International Society of Animal Genetics (ISAG) of 5.000×10-4 for parentage, and a combined non-exclusion probability for sib identity (NE-SI) of 2.679×10-5. Parentage analysis has been successfully identified the JBC offspring in the indigenous population and cattle farms used the certified AI semens for production using the JBC-derived offspring for commercial beef. This combined molecular marker system will be helpful to supply genetic information for parentage test and traceability and to develop the molecular breeding system for improvement of animal productivity in JBC population. KCI Citation Count: 2